ANALISIS SISTEM PENYALURAN PEMBIAYAAN KREDIT USAHA RAKYAT (KUR) TERHADAP USAHA MIKRO, KECIL DAN MENENGAH (STUDI KASUS DI PT. BANK RAKYAT INDONESIA UNIT SITUMEKAR) - Aprilianti, Alya; Nugroho, Gatot Wahyu; Nurodin, Idang (Universitas Nusantara PGRI Kediri, 2020)
This research was conducted based on the reason of the Kredit Usaha Rakyat (KUR) which is a government economic program that is held to help Usaha Mikro, Kecil, dan Menegah (UMKM) in order to overcome the existing economic problems, and become a solutions for job creation, to prevent poverty, unemployment and social inequality. This research is focused on procedure, implementation, and obstacles in the distribution of Kredit Usaha Rakyat (KUR) in Bank Rakyat Indonesia Sukabumi Branch Office Unit Situmekar to UMKM in the BRI Unit Situmekar work area. This research uses a descriptive qualitative method. Researchers use a primary and secondary data to do the analysis. In this research, researchers conducted several techniques to collect supporting data such as observation, interviews and documentation, then the researchers interactive patterns, including data collection, data reductions and do the conclusions. The results of this research shows that the step of procedure of distribute Kredit Usaha Rakyat towards UMKM is to apply for Kredit Usaha Rakyat in the nearest Bank Rakyat Indonesia office, Credit Analyisis, On The Spot, Preparing the credit files, then the money is credited to your saving account. At the time of distribution of Kredit Usaha Rakyat (KUR) there are several conditions that must be considered such as the debitur must not have a working capital loan, and the obstacle for the distribution is the condition of economics.